2022
DOI: 10.1093/ije/dyac015
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection fatality rate after the first epidemic wave in Mexico

Abstract: Background Estimates of SARS-CoV-2 infection fatality rates (IFRs) in developing countries remain poorly characterized. Mexico has one of the highest reported COVID-19 case-fatality rates worldwide, although available estimates do not consider serologic assessment of prior exposure nor all SARS-CoV-2-related deaths. We aimed to estimate sex- and age-specific IFRs for SARS-CoV-2 in Mexico. Methods The total number of people in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The impact of COVID-19 during the last 3 years has been substantial, and COVID-19 mortality is an important outcome indicator for monitoring the pandemic. These COVID-19 deaths and excess mortality estimates showing that persons aged ≥60 years accounted for more than 80% of total COVID-19 deaths even when controlling for income levels are consistent with the initial SARS-CoV-2–related mortality patterns described in China and subsequently by other countries ( 1 3 ). The large disparity observed between reported deaths and estimated excess mortality, especially in upper-middle–, lower-middle–, and low-income countries, makes ascertaining true COVID-19–associated mortality challenging.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The impact of COVID-19 during the last 3 years has been substantial, and COVID-19 mortality is an important outcome indicator for monitoring the pandemic. These COVID-19 deaths and excess mortality estimates showing that persons aged ≥60 years accounted for more than 80% of total COVID-19 deaths even when controlling for income levels are consistent with the initial SARS-CoV-2–related mortality patterns described in China and subsequently by other countries ( 1 3 ). The large disparity observed between reported deaths and estimated excess mortality, especially in upper-middle–, lower-middle–, and low-income countries, makes ascertaining true COVID-19–associated mortality challenging.…”
Section: Discussionsupporting
confidence: 78%
“…After the emergence of SARS-CoV-2 in late 2019, transmission expanded globally, and on January 30, 2020, COVID-19 was declared a public health emergency of international concern. * Analysis of the early Wuhan, China outbreak (1), subsequently confirmed by multiple other studies (2,3), found that 80% of deaths occurred among persons aged ≥60 years. In anticipation of the time needed for the global vaccine supply to meet all needs, the World Health Organization (WHO) published the Strategic Advisory Group of Experts on Immunization (SAGE) Values Framework and a roadmap for prioritizing use of COVID-19 vaccines in late 2020 (4,5), followed by a strategy brief to outline urgent actions in October 2021.…”
mentioning
confidence: 70%
“…Among these hospitalized patients, around 1% required mechanical ventilation and had an even higher lethality rate of around 80%. Analyzing patient demographics, age, and patient type are crucial factors in COVID-19 outcomes in Mexico [Torres-Ibarra et al, 2022]. Patients under the age of 65 who require hospitalization have a mortality rate of less than 50%, which increases significantly with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…Men have higher levels of Gompertzian Lethality than women but similar levels of Pasteurian Infectivity Gompertzian Analysis reveals that men have a higher level of COVID-19 Gompertzian Lethality (Deaths/Cases), in each age group, than women, taking the form of a higher Gompertzian Height, GH, with both sexes having a somewhat similar Gompertzian Slope, GS (APPENDIX-FIGURE 42). 7 There is no evident male/female difference in Pasteurian Infectivity (Cases/Population).…”
Section: Non-immunological Influences On Covid-19 Lethality and Infec...mentioning
confidence: 99%